The origin of tones in Latvian nominal suffixes - Rinkevičius, Vytautas (Baltistica, 2018)
The article deals with the origin and development of tones in Latvian nominal suffixes from a perspective of Balto-Slavic historical accentology. After establishing the Latvian prosodic reflexes of the accentual properties of reconstructed Balto-Slavic nominal suffixes and comparing the tones of a number of Latvian suffixes with the accentuation of their Baltic and Slavic cognates, their accentological reconstruction is provided. The tones of the majority of the analyzed Latvian suffixes correspond more or less regularly to the accentual properties of the reconstructed Proto-Baltic or Proto-Balto-Slavic suffixes and may therefore be directly derived from them. In the subsequent development of their tones, the following additional factors may have also played a role: a) the tendency to generalize the broken tone as a reflex of unstressed strong (“dominant”) acute suffixes in adjectives, and the sustained tone as a reflex of stressed strong acute suffixes in nouns (an indirect trace of the phenomenon called “Nikolaev’s metatony”); b) the influence of participles on adjectives with a similar morphological structure; c) generalization of the sustained tone before the glide j; d): generalization of the broken tone in reflexes of strong acute suffixes with the vowel ī (in Eastern dialects); e) generalization of the sustained tone which arose as a result of tonal dissimilation in the weak (“recessive”) suffixes with a particular phonological structure (in some dialects).
Keywords: Latvian; Balto-Slavic; historical accentology; nominal suffixes; tones